PENGARUH TINGKAT BUNGA DEPOSITO DAN RETURN SAHAM TERHADAP VOLUME PENJUALAN SAHAM PERUSAHAAN FARMASI DI BURSA EFEK INDONESIA - Rachmawati, Titiek (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2010)
The purpose of this research is to know the Time Deposit Rate, Stock Return that influence simultaneously or partially to the Sales Volume  in Indonesia Stock Exchange.        The research is causal comparative the data resource that were used from pharmaceuticals aunual report 2005 until 2007 from Indonesia Stock exchange . According to the criteria in this research, the samples are 5 pharmaceuticals  in industrial pharmaceuticals. For analysing the model and testing the research hypotheses, we used multiple linear regression analysis statistic method.          Based on the research result and the hypotheses test, we can conclude as follow : 1)   Time Deposit Rate, and Stock Return influence simultaneausly to the Sales Volume2)   Stock Return influence partially to the Sales Volume while Time Deposit Rate had proved not influence. Keywords : Time Deposit Rate, Stock Return, Sales Volume